Constitutional crisis: case studies in the decentralised public administration of education in South Africa (2011-2015) - Chilenga-Butao, Thokozani Jean (My University, 2019)
South Africa’s decentralised governance is in a constitutional crisis. This crisis is caused by the lack of an explicit naming and conceptualisation of decentralisation in the Constitution of the Republic of South Africa, 1996. Instead, the country relies on an implicit assumption that the state is a decentralised unitary state, which is reflected in the Constitution and ensuing legislation and regulations. The constitutional crisis is precipitated by the fact that mechanisms of decentralisation, known as constitutional interventions in Sections 100 & 139 of the Constitution, are also not fully regulated or clarified. As a result, attempts to resolve public administration crises in decentralised provincial administrations has failed. This is evident in the provincial education departments of Limpopo (LDE) and the Eastern Cape (ECDE). In the LDE, the implicit nature of South Africa’s decentralisation produces a legislative gap in the implementation of S100 (1) (b). This legislative gap compounds the existing constitutional crisis because it lacks procedural clarity, confuses S100 as a mechanism and provides loopholes for exploitation of the process. These loopholes, in turn, distort and lengthen resolutions for public administration crises in provincial governance. In the ECDE, South Africa’s constitutional crisis is compounded by the structural institutional crisis in that provincial education department. This department has experienced waves of colonial, apartheid and democratic decentralisation, which have produced layers of lack of capacity, internal factionalism and chronic mismanagement. In this context, the constitutional crisis becomes a red herring for structural institutional weaknesses in the province. In both case studies, the S100 (1) (b) did not develop or strengthen the problem-solving capabilities of these provincial education departments. This thesis examines South Africa’s constitutional crisis in decentralisation using a multidisciplinary approach that relies on political theory, African and South African history, administrative and applied political studies perspectives to explore the constitutional crisis and provides practical recommendations to follow.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy Department of Political Studies, School of Social Sciences University of the Witwatersrand August 2019
Keywords: Educational accountability; Public administration--Study and teaching; Education